2016
DOI: 10.18869/acadpub.jafm.68.225.24447
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Slip Velocity and Roughness on the Jenkins Model Based Ferrofluid Lubrication of a Curved Rough Annular Squeeze Film

Abstract: This paper theoretically analyzes the combined effect of slip velocity and surface roughness on the performance of Jenkins model based ferrofluid squeeze film in curved annular plates. The effect of slip velocity has been studied resorting to the slip model of Beavers and Joseph. The stochastically averaging method of Christensen and Tonders has been deployed for studying the effect of surface roughness. The pressure distribution is derived by solving the associated stochastically averaged Reynolds type equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…When normalΩu0 and normalΩl0 (i.e., there is no rotation of the upper sphere or lower plate), the present study reduces the findings of Patel and Deheri. 22 In their study, they evaluated combined effects of surface roughness and slip velocity on the Jenkins model based ferrofluid lubrication of a curved rough annular squeeze film. When applying the Jenkins model to magnetic fluid flow, it was found that combined effects of negatively skewed roughness and variance delay in justifying the adverse influence of slip velocity and standard deviation.4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When normalΩu0 and normalΩl0 (i.e., there is no rotation of the upper sphere or lower plate), the present study reduces the findings of Patel and Deheri. 22 In their study, they evaluated combined effects of surface roughness and slip velocity on the Jenkins model based ferrofluid lubrication of a curved rough annular squeeze film. When applying the Jenkins model to magnetic fluid flow, it was found that combined effects of negatively skewed roughness and variance delay in justifying the adverse influence of slip velocity and standard deviation.4.…”
Section: Resultsmentioning
confidence: 99%
“…Equations of the basic flow for the motion of ferrofluids in the film region, based on ferrohydrodynamic theory governed by Jenkins model with continuity equation in cylindrical polar coordinates (r,θ,z) are given by 16,22,28 andwhere η is the fluid viscosity, p is the film pressure p , is the fluid density, μ¯ is the magnetic susceptibility, μ¯0 is the initial susceptibility of fluid, μ0 is the permeability of free space, q is the fluid velocity vector, boldH is the applied magnetic field vector, boldM is the magnetization vector, M is the magnitude of magnetization vector, boldM is the co-rotational derivative of M, Ms is the saturation mag...…”
Section: Formulation Of the Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Xiujiang Shi conducted numerical analysis of EHL under different carrier fluid ferrofluids lubrication of sliding bearing systems. Patel et al used the Jenkins model to address the influences of field strength, slip velocity, and surface roughness on squeeze films. Tipei, Shah, and Chi et al discovered that higher field strength could mean higher carrying capacity for magnetic liquids.…”
Section: Introductionmentioning
confidence: 99%